Análise produtiva de genótipos de milho-verde consorciados com feijão - Carvalho, Islan D. E.; Ferreira, Paulo V.; Silva Júnior, Antonio B.; Teixeira, Jadson S.; Oliveira, Felipe S. [UNESP]; Carvalho, Artur P. V.; Santos, Paulo R. (FapUNIFESP (SciELO), 2016)
We analysed the productivity of green maize genotypes intercropped with beans. The experiment was carried out at Centro de Ciências Agrárias of Universidade Federal de Alagoas,Maceió,Brazil,using the randomized blocks design in a factorial scheme (4x2),with four maize genotypes (Alagoano,Viçosense,Nordestino and Cruzeta) and two cropping systems (monoculture and intercropped),plus a complementary treatment (IAC Alvorada beans in monoculture),in three blocks. Desirable agronomic variables were evaluated for the production of green beans and corn. The genotypes Viçosense,Nordestino and Alagoano presented the highest marketable ears productivity,with an average of 12.28 t/ha,and high quality characteristics of corn. The intercropping of corn and beans presented the same marketable characteristics as those obtained with corn in monoculture (11.50 t/ha). The indexes of maize productive efficiency and efficient use of the land presented values,respectively of 0.92 and 1.39,confirming the viability of the intercropping,beyond the potential of the genotypes to be used in this system.
Productive analysis of green maize genotypes intercropped with beans
Keywords: Association of cultures; Phaseolus vulgaris; Zea mays